2014
DOI: 10.1111/adb.12155
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain functional networks in heavy smokers

Abstract: Recent neuroimaging studies have demonstrated that cigarette smoking is associated with changed brain structure and function. However, little is known about alterations of the topological organization of brain functional networks in heavy smokers. Thirty-one heavy smokers and 33 non-smokers underwent a resting-state functional magnetic resonance imaging scan. The whole-brain functional networks were constructed by thresholding the correlation matrices of 90 brain regions and their topological properties were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 49 publications
6
45
1
1
Order By: Relevance
“…Other RSN groups affected by both smoking and drinking were ECN, SAL and PRE indicating the existence of common effects across the brain. These results agree with the detriment of network global efficiency previously observed in both smokers (Fedota and Stein, 2015; Lin et al, 2015) and drinkers (Sjoerds et al, 2015). Few differences were detected when the post-hoc analysis in our data compared rsFNC differences of SAD vs. DRN and SAD vs. SMK groups indicating that common effects cannot differentiate between the substances.…”
Section: Discussionsupporting
confidence: 92%
“…Other RSN groups affected by both smoking and drinking were ECN, SAL and PRE indicating the existence of common effects across the brain. These results agree with the detriment of network global efficiency previously observed in both smokers (Fedota and Stein, 2015; Lin et al, 2015) and drinkers (Sjoerds et al, 2015). Few differences were detected when the post-hoc analysis in our data compared rsFNC differences of SAD vs. DRN and SAD vs. SMK groups indicating that common effects cannot differentiate between the substances.…”
Section: Discussionsupporting
confidence: 92%
“…We would like to emphasize that we cannot formally exclude a possible alternative explanation that these alterations are a trait of people who smoke, as opposed to people who do not smoke. These connectivity results are in line with a recent study showing decreased connectivity in active smokers versus non-smokers between dorsolateral prefrontal cortex and parietal nodes that are part of the executive control network (ECN) (Weiland et al 2014) and another study which found decreased global efficiency (a measure that takes into account connectivity) in heavy smokers compared with non-smokers (Lin et al 2014). Moreover, our findings are consistent with studies on other forms of addiction, including opioids (Liu et al 2009;Upadhyay et al 2010;Ma et al 2011) and Internet addiction (Hong et al 2013), where a lower functional connectivity is present in addicted subjects.…”
Section: Discussionsupporting
confidence: 91%
“…A small sample of cocaine‐dependent individuals show reduced local efficiency (Wang et al 2015). However, the opposite pattern has been demonstrated in nicotine dependence, of enhanced local efficiency and reduced global efficiency (Lin et al 2015). Furthermore, a previous study reported no difference in local or global efficiency in heroin dependence (Jiang et al 2013a).…”
Section: Introductionmentioning
confidence: 99%